2019
DOI: 10.1111/iji.12451
|View full text |Cite
|
Sign up to set email alerts
|

Single‐nucleotide polymorphisms associated with pemphigus vulgaris: Potent markers for better treatment and personalized medicine

Abstract: Pemphigus vulgaris (PV) is a rare autoimmune blistering disorder, which could affect both skin and mucosal surfaces. There is increasing evidence that genetics plays a critical role in PV development, severity and prognosis. Single‐nucleotide polymorphisms (SNPs) are the most common type of genetic variation among people and have been widely evaluated in most diseases. However, there are few studies regarding the roles of SNPs in the PV. Here, we reviewed both pathogenic and protective roles of the SNPs in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…6,7 Association of some gene polymorphisms of immune-mediated genes and cytokines with pemphigus had been shown in several studies. 8 Also, several studies have demonstrated the differences between sera cytokines levels of pemphigus patients and healthy controls (systematically reviewed by Tavakolpour et al 9 ), while there are limited reports regarding different genes' expression profile in comparison with healthy controls. The expression of NLRP1, 10 IPAF, 10 CD19 genes, 11 and some miRNAs including miR-424-5p 12 and miRNA-338-3p 13 were demonstrated to be significantly increased in blood samples of PV and/or PF patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Association of some gene polymorphisms of immune-mediated genes and cytokines with pemphigus had been shown in several studies. 8 Also, several studies have demonstrated the differences between sera cytokines levels of pemphigus patients and healthy controls (systematically reviewed by Tavakolpour et al 9 ), while there are limited reports regarding different genes' expression profile in comparison with healthy controls. The expression of NLRP1, 10 IPAF, 10 CD19 genes, 11 and some miRNAs including miR-424-5p 12 and miRNA-338-3p 13 were demonstrated to be significantly increased in blood samples of PV and/or PF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation, activation, proliferation, and function of immune cells are controlled by the immune mediators, such as cytokines and immune checkpoints 6,7 . Association of some gene polymorphisms of immune‐mediated genes and cytokines with pemphigus had been shown in several studies 8 . Also, several studies have demonstrated the differences between sera cytokines levels of pemphigus patients and healthy controls (systematically reviewed by Tavakolpour et al 9 ), while there are limited reports regarding different genes' expression profile in comparison with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…18 The CTLA4 rs231775 variant has been reported to be associated with various autoimmune diseases such as Graves' disease in adults 24 and autoimmune hypothyroidism in children of the Han Chinese population, 25 multiple sclerosis, 26 vitiligo, 7 vasculitis, 27 systemic lupus erythematosus, [28][29][30] rheumatoid arthritis, 31,32 latent autoimmune diabetes in adults, 33 primary biliary cirrhosis, 34 primary biliary cholangitis, 35 and Pemphigus Vulgaris. 36,37 Additionally, a more recent meta-analysis by Wang and colleagues indicated a significant association of CTLA4 rs231775 with autoimmune diseases' susceptibility under different genetic models, highlighting its potential implication as a diagnostic genetic biomarker in both Asian and Caucasian populations. 38 However, our results are not consistent with Song et al and Liang et al meta-analyses 8,9 and partially agree with Birlea et al 4 The latter study showed no association of the specified variant with vitiligo in the overall analysis; however still, a significant one was evident in vitiligo patients with other concomitant autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of alleles of DRB1*14/DQB1*05 and A*11/DQB1*05 would be strongly influential for the predisposition to the disease, while that of HLA-B*50/DQB1*02 could play a protective role [14]. In addition, multiple single nucleotide polymorphisms within different genes may confer susceptibility to the diseases, probably in a population-specific way [15]. Serological typing for HLA class II antigens in patients with ABD of the pemphigoid type revealed a highly significant association with HLA-DQβ1*0301 [16].…”
Section: Geneticsmentioning
confidence: 99%